Multifunctional Hybrid Materials Based on Polymers: Design and Performance - Hamzehlou, Shaghayegh; Aboudzadeh, M. Ali (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Multifunctional hybrid materials based on polymers have already displayed excellent commitment in addressing and presenting solutions to existing demands in priority areas such as the environment, human health, and energy. These hybrid materials can lead to unique superior multifunction materials with a broad range of envisaged applications. However, their design, performance, and practical applications are still challenging. Thus, it is highly advantageous to provide a breakthrough in state-of-the-art manufacturing and scale-up technology to design and synthesize advanced multifunctional hybrid materials based on polymers with improved performance.The main objective of this interdisciplinary book is to bring together, at an international level, high-quality elegant collection of reviews and original research articles dealing with polymeric hybrid materials within different areas such as the following:- Biomaterials chemistry, physics, engineering, and processing;- Polymer chemistry, physics and engineering;- Organic chemistry;- Composites science;- Colloidal chemistry and physics;- Porous nanomaterials science;- Energy storage; and- Automotive and aerospace manufacturing.